MANAJEMEN SEKOLAH DI ERA DIGITAL: Optimalisasi Kepemimpinan Transformasional untuk Peningkatan Kinerja Guru di Indonesia - Alfasius Tobondo, Yuyun (Yayasan Sukma, 2025)
The digitalization of education has transformed the learning and school management landscape, requiring adaptive leadership to ensure the effective implementation of technology. However, many school principals still rely on administrative and transactional leadership styles, which do not fully support innovation and digital adaptation. This study aims to analyze the impact of transformational leadership on improving teacher performance in increasingly digitalized school environments. A literature review was conducted to examine research related to transformational leadership, educational digitalization, and factors influencing teacher performance. The findings indicate that transformational leadership plays a crucial role in fostering a conducive environment for teachers to adapt to technology, enhance work motivation, and optimize the effectiveness of digital-based learning. However, challenges such as disparities in access to digital infrastructure and low levels of technological literacy remain major obstacles to implementation. Therefore, policies are needed to support the development of transformational leadership in schools, enhance teachers' capacity in utilizing technology, and provide adequate infrastructure. This study provides valuable insights for school principals, policymakers, and stakeholders in designing more innovative and technology-responsive leadership strategies in the education sector. Keywords: Digitalization of education, transformational leadership, teacher performance, school management, educational technology